Strategi Guru Dalam Menangani Anak Yang Mengalami Keterlambatan Dalam Berbahasa (Observasi Lapangan Di TK Daarul Fattaah Tangerang) - Maratus Sholihah; Maulida Fitriani; Mia Istiqamah (Fakultas Tarbiyah IIQ Jakarta, 2022)
The world health organization states that children aged 0-6 years are said to be in the golden age. This happens because the process of growth and development of children occurs rapidly in the span of development of human life. In this golden period, children learn by seeing, hearing, and feeling what is happening around them. In dealing with quiet children, as a teacher at school, special attention is needed, such as asking children to express their opinions more or trying to answer one or two questions that are telling a thing (experience) that makes children talk more and are no longer afraid to convey something. what he's been through. Speech disorders consist of problems with articulation, voice, fluency (stuttering), difficulty in using words, usually due to brain injury and delay in speaking. Children who have delays in speaking can be caused by various factors, one of which is environmental factors or hearing loss. Speech disorders are also closely related to other developments.